Emerging Non-Pharmacological Refractory Intervention for Pain Relief in Fibromyalgia: A Case Report - Al-Zoubi, Saif; Alsabbah, Alameen; Wassouf, Maggie; Al-Mnayyis , Asmaa (Scripta Medica, 2023)
Fibromyalgia (FM) is a common disorder characterised by widespread musculoskeletal pain often associated with fatigue, sleep, memory and mood disturbances. Females are more likely to suffer from FM and experience a reduced quality of life. This is a case report of a 21-year-old female patient diagnosed with FM whose pain was managed by a non-pharmacological method, weightlifting exercises. The patient suffered from chronic generalised muscular pain, muscle stiffness, fatigue, depression and anxiety. She was started on a tight progressive weight-lifting program to increase muscle mass. The program led to a resolution of symptoms after 3 months of gradual improvement, in addition to stopping taking analgesics for the pain. Notably, a relapse occurred after halting the exercise program suggesting that the weight-lifting regime was correlated to reducing symptom severity and better quality of life. Exercises involving weight-lifting could potentially provide an affordable treatment option for patients with FM.